P34 ASYMPTOMATIC VENTRICULAR PRE–EXCITATION WITH DISAPPEARANCE DURING EXERTION: ALWAYS AN INDEX OF BENIGNITY?. (18th May 2022) - Barengo, A; Parise, A; Notaristefano, F; Sforna, S; Padoan, L; Bernardini, G; Notarianni, G; D'ammando, M; Zingarini, G; Cavallini, C
Abstract: Introduction: The disappearance of pre–excitation at high heart rates points to a low arrhythmic risk: why resort to electrophysiological studies anyway? Clinical Case: L.S., a 12–year–old patient, performed an ECG for sports examination with evidence of ventricular pre–excitation from an asymptomatic left lateral accessory route (Fig. A ). A 24 h ECG–Holter during training showed the disappearance of the pre–excitation at high frequencies (Fig. B ) which is considered a low risk index. The patient underwent a transesophageal electrophysiological study (SETE) during which an effective refractory antegrade period of 228 ms of the pathway was objectified through atrial extrastimuli (*) (Fig. C : drive of atrial stimuli (*) followed by extrastimulus with conduction on an accessory route (E)). In addition, a 1: 1 conduction was observed on the atrial pathway up to at least 270 bpm (222 ms). The antegrade refractory period of the resting path was <250 ms and therefore identified a high–risk condition to be treated with ablation. Discussion: The disappearance of pre–excitation at high heart rates is usually considered indicative of an accessory pathway with a long refractory period and therefore at low risk, however it must be sudden. According to European guidelines, the execution of invasive studies in asymptomatic patients who are employed in high–risk jobs or competitive sports has a class I B indication, but in the remaining asymptomatic cases the indication is IIa B. The Holter ECG alone or the stress test, with a careless evaluation of the disappearance of the pre–excitation (sudden vs progressive with minimal residual pre–excitation) would have erroneously led to labeling this accessory pathway at low risk. In the left lateral accessory pathways, with the increase of the HR, there can be a disappearance or pseudo–disappearance of the pre–excitation for anatomical reasons (being further away from the SA node) and for an increase in the AV conduction speed, not therefore for a long refractory period of the pathway. SETE is closer to the atrial side of the left accessory pathway and allows to correctly classify the risk. Conclusion: SETE is a low–cost and minimally invasive method that should be considered as an integral part of the study of patients with asymptomatic ventricular pre–excitation even if non–invasive stratification indicates low risk.